Tożsamość seryjnego mordercy. Przypadek Joachima Knychały na podstawie literatury non-fiction (Heteroglossia – studia kulturoznawczo-filologiczne, 2017)
The goal of this lecture is to attempt to answer the question dealing with the identity of a serial killer – Joachim Knychała and to watch narrations about him. Presentation and characteristics of identity Knychały serve literature non-fiction. The identity of the serial killer is shaped by both sides: internally, as his self-awareness and thus determine the individual experience of unhappiness, trauma, exclusion, condemnation and externally i.e. from the point of view of behaviour socially acceptable and at the time identity is determines as a fact of maladjustment or exceeding the social norms. The summary of discussion will attempt to answer the question about phenomenon of serial killer.